Les recherches sur le jeu vidéo en France - Sarah Meunier (Revue d'anthropologie des connaissances)
This article introduces the actual French group of research of video games in Human and Social Sciences, by interrogating its emergence from international Game Studies. It is founded on a set of interviews, on a socio-historic study based on private and online archives, as well as a selected corpus of relevant articles. This piece of work shows three principal elements. It treats the research object’s legitimization that impacts the research development. It presents and analyses the 20 years growing researchers’ group by focusing on the nature of the social links. At least, it focuses on presence or lack of links between the French group and the Game Studies, emphasizes on the aspects that might show French research autonomy.